2017
DOI: 10.1123/jsr.2015-0130
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Ankle Position During the Nordic Curl on Muscle Activity of the Biceps Femoris and Medial Gastrocnemius

Abstract: Ankle position does not influence muscle activity during the Nordic curl; however, performance of Nordic curls with the ankle in a DF position may be preferential, as this replicates the ankle position during terminal leg swing during running, which tends to be the point at which hamstring strains have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 19 publications
3
17
0
3
Order By: Relevance
“…Our data may partially support this assertion, as the range and degree of correlations were slightly higher in the supine, hip neutral position as compared to the seated position. Inter-rater reliability of the NordBord exceeded the previously published values and is comparable to those observed by Lodge et al 56 for the Hamstring Solo dynamometer. Consequently, the NordBord shows high test-retest reliability and a moderate correlation with isometric knee flexion assessed with the BD.…”
Section: Effect Of Hip and Ankle Position On Knee Flexor Isometric Strengthsupporting
confidence: 88%
See 1 more Smart Citation
“…Our data may partially support this assertion, as the range and degree of correlations were slightly higher in the supine, hip neutral position as compared to the seated position. Inter-rater reliability of the NordBord exceeded the previously published values and is comparable to those observed by Lodge et al 56 for the Hamstring Solo dynamometer. Consequently, the NordBord shows high test-retest reliability and a moderate correlation with isometric knee flexion assessed with the BD.…”
Section: Effect Of Hip and Ankle Position On Knee Flexor Isometric Strengthsupporting
confidence: 88%
“…The authors attributed this to the characteristics of the tasks, whereby the hip is in a relatively neutral position during the Nordic hamstring curl opposed to seated knee flexion, and the bilateral nature of the Nordic hamstring curl as compared to unilateral isokinetic measures. Conversely, Lodge et al 56 assessed a comparable Nordic dynamometer (Hamstring Solo Elite) and found an inter-device correlation of 0.823 and 0.840 between the left and right limbs with isokinetic eccentric knee flexion torque at 30 o /s. Our data may partially support this assertion, as the range and degree of correlations were slightly higher in the supine, hip neutral position as compared to the seated position.…”
Section: Effect Of Hip and Ankle Position On Knee Flexor Isometric Strengthmentioning
confidence: 99%
“…Data regarding the 114 exercises are available in Supplementary Table S2. This figure highlights both NHEs from Comfort et al [52] and barbell deadlifts from Andersen et al [59] with biceps femoris activation higher than 100% MVIC. Moreover, the slip leg exercise and the heel strike against ball exercise from Arias-Poblete et al [39] achieved 99% and 94% of BFlh activation, respectively.…”
Section: Muscle Activationmentioning
confidence: 74%
“…For this purpose, a maximal voluntary contraction of the BF and ST was performed with the participant lying prone, with a knee flexion angle of 45º and a hip angle of 0º. 23 The lower leg was fixed in position and each participant completed three, five second maximal contractions whilst muscle activation was recorded. With the knee fixed at 90º flexion and the hip at 0º, 24 three further maximal contractions were performed for five seconds, to determine the maximal activation of the GM muscle.…”
Section: Methodsmentioning
confidence: 99%